(3GdJHjGf aj HjGf eG aj djdI GdfUa ef TYHGf hdjdI GdbOQ ef QeVGfs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bOQ GdCQRGb hGdBLGd CeG HYO ajbhd Ef HYV CNhGf CdJeS efi Cf CcJH HYV eG jJYdb HdjdI GdfUa ef TYHGf Ydi hLg jajO HjGf djdI GdbOQ s
(3BNQgG (B:s
(3jhe fdbGg hLeY HjffG hHjf CQHGH GdLeY ai NOeI ehdGg hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs